2010
DOI: 10.1371/journal.pone.0015962
|View full text |Cite
|
Sign up to set email alerts
|

A New Peptide Ligand for Targeting Human Carbonic Anhydrase IX, Identified through the Phage Display Technology

Abstract: Carbonic anhydrase IX (CAIX) is a transmembrane enzyme found to be overexpressed in various tumors and associated with tumor hypoxia. Ligands binding this target may be used to visualize hypoxia, tumor manifestation or treat tumors by endoradiotherapy.MethodsPhage display was performed with a 12 amino acid phage display library by panning against a recombinant extracellular domain of human carbonic anhydrase IX. The identified peptide CaIX-P1 was chemically synthesized and tested in vitro on various cell lines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 30 publications
2
35
0
2
Order By: Relevance
“…Screening of phage display libraries, 8,23 CAD, 10 hydropathic complementarity, 24 hydropathic analysis, and comparative sequence/structure analysis 7 have been used to design small peptide ligands. In this study, we demonstrated different methods of screening for small molecule peptide ligands.…”
Section: Discussionmentioning
confidence: 99%
“…Screening of phage display libraries, 8,23 CAD, 10 hydropathic complementarity, 24 hydropathic analysis, and comparative sequence/structure analysis 7 have been used to design small peptide ligands. In this study, we demonstrated different methods of screening for small molecule peptide ligands.…”
Section: Discussionmentioning
confidence: 99%
“…This approach has been used in various applications, such as in the mapping and mimicking of epitopes, the identification of new receptors and natural ligands, high-affinity antibodies and analogs, the isolation of specific antigens binding to bioactive compounds, the production of novel enzyme inhibitors and DNA-binding proteins, and the probing of cellular and tissue-specific processes. Phage display has been successfully applied for the identification of peptides with a high specificity for target tumor neovasculature or a variety of human tumor cells (16,(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33).…”
Section: Biotechnology Methods For Identification Of New Ligands: Dismentioning
confidence: 99%
“…This degradation inevitably leads to a stability problem, with a plasma half-life in the range of several minutes (26)(27)(28)(29)(30). Stability may be increased by shortening the peptide after identification of the essential binding sequence using an alanine scan, exchange of single amino acids, introduction of D-amino acids, peptide cyclization, and coupling to chelators such as DOTA.…”
Section: Affinity and Stability Or Scylla And Charybdis: Is There A Smentioning
confidence: 99%
“…Phage display has successfully been applied for the identification of novel peptides with high specificity for target proteins overexpressed in the tumor neovasculature, such as delta-like ligand 4 (Dll4), or for human lung carcinoma, mammary carcinoma, prostate carcinoma and neuroblastoma cells [1,2,[21][22][23][24][25][26].…”
Section: Display Systemsmentioning
confidence: 99%